Night Eating Syndrome in Patients With Obesity and Binge Eating Disorder: A Systematic Review - Kaur, Jasmine; Dang, An Binh; Gan, Jasmine; An, Zhen; Krug, Isabel (Frontiers in Psychology, 2022)
Night eating syndrome (NES) is currently classified as an Other Specified Feeding or Eating Disorder (OSFED) under the Diagnostic Statistical Manual-5 (DSM-5; APA, 2013). The aim of this systematic review was to consolidate all studies assessing NES in eating disorder (ED) patients, obese patients and bariatric surgery patients, since the publication of the DSM-5 (APA, 2013) in 2013. A further aim was to appraise the quality of the studies being included in the review. A total of 22 studies across three population groups – ED (including NES), obese and bariatric surgery patients - meeting the inclusion criteria were included in this review. The main findings of our study revealed that no conclusions about the link between any sociodemographic feature (such as age or gender) and an NES diagnosis could be made. Further, NES patients presented with elevated ED pathology (including emotional eating and loss of control eating) and higher occurrence of depressive symptoms than controls. The literature suggests that NES and binge eating disorder (BED), an eating disorder (ED) subtype which is also comorbid with obesity, are often found to have overlapping features questioning the validity of NES as an ED diagnosis. However, we found that BED was differentiated from NES by the higher occurrence of emotional eating, body related concerns and abnormal eating episodes. The review also suggested an overlap between NES and sleep-related eating disorder. We recommend that it is essential to study NES as an independent disorder to further develop its diagnostic criteria and treatment options, thereby, increasing the quality of life of the patients suffering from this syndrome.